Effects of local abundance on pollination and reproduction in Delphinium fissum subsp. sordidum (Ranunculaceae). Issue 4 (2nd October 2017) - Ramírez-Rodríguez, Rubén; Amich, Francisco
Abstract: Delphinium fissum subsp. sordidum (Ranunculaceae) is an endangered, xenogamous, self-compatible hemicryptophyte endemic of the central-western Iberian Peninsula, with a disjunct distribution in the Sierra Mágina (Spain: Jaén Province). We studied the effects of local abundance, in terms of plot size (number of individuals) and plot purity (relative abundance), assessing the activity of pollinators (frequency of visits and behaviour of visitors), quantity and quality of pollinator services and seed set in two populations. Flowers of D. fissum subsp. sordidum were visited by Hymenoptera (88.8%), Lepidoptera (10.3%) and Diptera (0.9%). The most frequent pollinator was Bombus terrestris (72.6% of total visits). Differences in relative frequency of visits to plants were observed between populations. Plots with high numbers of individuals attracted more pollinators. The same pattern was observed for stigmatic pollen loads and seed set; 99.46% of pollen grains deposited on the stigmas were conspecific, and the main competitor was Ferula communis . The effects of purity were assessed by comparing pure plots with a mixed plot that included plants that coincide with the flowering stage of D. fissum subsp. sordidum and exert an effect of interspecific competition. These results may be useful for developing conservation measures, especially in the small population of Aldeadávila.